2023
DOI: 10.3390/sym15030700
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry as a Measure of Stress in Natural Populations of Woody Plants: Influence of Ecological and Geographical Factors on Developmental Stability

Abstract: Fluctuating asymmetry is a sensitive indicator of favorable conditions during the period of individual development. The influence of climatic factors, biotopic conditions, latitude, altitude, and age of plants from the natural populations of the silver birch Betula pendula Roth was analyzed. The material consisted of 13,000 leaves of the silver birch from 11 regions of north-eastern Siberia. The influence of 23 climatic factors and six integrated coefficients characterizing the general suitability of the clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In urban conditions in individuals of different ages B. pendula shows an ambiguous reaction to a complex of urban factors, which leads to the activation of growth processes. This phenomenon can be explained both by elevated temperatures and increased carbon dioxide content in the air, and by the use of pollutants by trees as additional elements of mineral nutrition [10,22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban conditions in individuals of different ages B. pendula shows an ambiguous reaction to a complex of urban factors, which leads to the activation of growth processes. This phenomenon can be explained both by elevated temperatures and increased carbon dioxide content in the air, and by the use of pollutants by trees as additional elements of mineral nutrition [10,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Tree plantings are an important object of urban ecosystem formation as well as a valuable indicator of the state of the environment. Researchers more often use various morphometric indicators of vegetative and generative organs of plants as bioindicative signs, less oftenchanges in the rhythms of their seasonal development [3][4][5][6][7][8][9][10]. In the works of the populationontogenetic direction [1,11,12] it is shown that the heterogeneity of the rhythms of seasonal development of individuals of one cenopopulation can be a mechanism of adaptation to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%